Smoke-Free Home and Vehicle Policies Among Community College Smokers. (August 2018) - Ossip, Deborah J.; Johnson, Tye; Assibey-Mensah, Vanessa; Wang, Sijiu; McLaren, Donald; Calabro, Karen; Prokhorov, Alexander V.; McIntosh, Scott
Background. Personal smoke-free policies (home and vehicle) reduce secondhand smoke exposure, improve health, and increase quitting among smokers. Overall, 83.0% and 78.1% of Americans report smoke-free homes and vehicles, respectively. However, little is known about such policies among 2-year community college (CC) students, who represent a large, diverse population with higher smoking rates and less negative attitudes toward smoking than 4-year college students. Methods. Prevalence of, and factors associated with, personal smoke-free policies were examined for 2, 475 CC smokers enrolled in a national trial of web-assisted tobacco intervention. Results. Few students had smoke-free home policies (20.7%), smoke-free vehicles (17.0%), both smoke-free home and vehicle policy (4.2%), or any policy (home or vehicle; 31.2%). In logistic regression models, having children was associated with a smoke-free home or any policy but not with a smoke-free vehicle, and among participants who had children, only 20% reported a smoke-free home, and only 15% had a smoke-free vehicle. In addition, not living with other smokers, living with parents or roommates/siblings (vs. alone), smoking later than 30 minutes after awakening, believing that smoking affects the health of others, and confidence in quitting were associated with presence of a smoke-free home or any policy; no variables were significantly associated with presence of a smoke-free vehicle. Conclusions. CC students represent a priority population for intervention regarding smoke-free homes and vehicles. Such intervention can decrease exposure of others, including children, and potentially increase the likelihood of quitting in this high-risk population.